Keputusan Pembelian Smartphone Oppo Berdasarkan Kualitas Produk, Inovasi Produk dan Citra merek (Studi Pada Mahasiswa Universitas Trunojoyo Madura) - Adriansyah, Agung; Andriani, Nurita (Management Department of Economics and Business Of Trunojoyo Madura University, 2023)
The purpose of this study was to determine the effect of product quality, product innovation, and brand image on product purchasing decisions smartphone OPPO on Trunojoyo Madura University students. This research is a quantitative research with a survey method through a questionnaire. The population in this study were students at Trunojoyo Madura University who had purchased the productsmartphone OPPO. The sample used in the study was 100 respondents using techniquespurposive sampling. The data analysis technique used to prove the hypothesis was compiled using multiple linear regression analysis. The results of the study show that product quality influences purchasing decisions. Product innovation has no effect on purchasing decisions. Brand image influences purchasing decisions.